ANALISIS KESALAHAN BERBAHASA TATARAN MORFOLOGI DI RUANG PUBLIK KELURAHAN MAYANG MANGURAI KOTA JAMBI - Reza Dwi Permatasari; Rasdawita Rasdawita; Rahmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to identify morphological language errors found in public spaces media in Mayang Mangurai Village, Jambi City, and describe appropriate corrections based on Indonesian language rules. This research used a qualitative descriptive approach. Data were collected through observation, documentation, and note-taking techniques on billboards, banners, posters, and other public information media. The results show that morphological errors are still frequently found, especially affixation errors, incorrect word formation, and inappropriate use of standard Indonesian forms. The findings indicate that affixation errors are the most dominant type. This study contributes to improving public awareness and the quality of Indonesian language use in public spaces. Keywords: language errors, morphology, public space